2018
DOI: 10.1016/j.cub.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Selective Attention Controls Olfactory Decisions and the Neural Encoding of Odors

Abstract: Critical animal behaviors, especially among rodents, are guided by odors in remarkably well-coordinated manners, yet many extramodal sensory cues compete for cognitive resources in these ecological contexts. That rodents can engage in such odor-guided behaviors suggests that they can selectively attend to odors. Indeed, higher-order cognitive processes-such as learning, memory, decision making, and action selection-rely on the proper filtering of sensory cues based on their relative salience. We developed a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 60 publications
(79 reference statements)
3
40
0
Order By: Relevance
“…Generally, these studies have shown that, under demanding sensory conditions, A1 neuron responses and/or tuning are enhanced, consistent with findings across PSC modalities (Carlson et al, 2018;Gomez-Ramirez et al, 2016;Mineault et al, 2016).…”
Section: Introductionsupporting
confidence: 83%
“…Generally, these studies have shown that, under demanding sensory conditions, A1 neuron responses and/or tuning are enhanced, consistent with findings across PSC modalities (Carlson et al, 2018;Gomez-Ramirez et al, 2016;Mineault et al, 2016).…”
Section: Introductionsupporting
confidence: 83%
“…As olfactory cortex, it receives direct input from the olfactory bulb, though unlike other olfactory cortical areas, it does not send a return projection to the bulb (In't Zandt et al, 2019). It is heavily interconnected with sensory, cognitive, hormonal, and reward-related regions of the brain (Xiong and Wesson, 2016) and maybe involved in attention to odors (Carlson et al, 2018) and odor-induced motivation (Murata et al, 2015), as might be expected given its strong link to dopaminergic reward and motor circuits (Ikemoto, 2007). The rodents OT is also monosynaptically connected with the amygdala and hypothalamus.…”
Section: Neural Circuits and Odor Perceptionmentioning
confidence: 99%
“…Both spatial and temporal coding strategies face the challenge that odour perception is dynamic and varies under different brain states. Wakefulness, attention, experience, metabolism status and the value of the odour for the subject are important factors that can change the perception of the same odour . The underlying mechanisms by which the OB represents odour information precisely under different brain and behavioural states remain elusive, although recent studies have provided relevant data and some hypotheses have been established .…”
Section: Introductionmentioning
confidence: 99%